Geology of the Kathmandu fluviatile lacustrine sediments in the light of new vertebrate fossil occurrences - Dangol, Gopal M. S. (Journal of Nepal Geological Society, 1985)
The fluviatile lacustrine sediments of the Kathmandu Valley have been restudied. New fossil discoveries in the southern part of the valley sheds light on the geology of the Kathmandu Valley. The finds comprise, diverse vertebrate fossils represented by elephant, deer, bovine and pig belonging to Plio-Pleistocene age. The paper mainly deals with stratigraphy of the Lukundol Formation and evolution of the Kathmandu sediments.